Advances in fibre Bragg grating technology for magnetic field sensing: A review - Rostami A.; Wahaab F.A.; Soleimani H.; Sikiru S.; Khosravi V.; Yusuff A.O.; Hamza M.F. (Elsevier B.V., 2024)
Magnetic field sensing is crucial for various scientific and technological applications, but current methods have limitations in cost, size, and weight. Fiber Bragg Grating (FBG) magnetic field sensors have emerged as a promising alternative, offering compact size, and simplified fabrication. This review introduces FBG synthesis methods and extensively discusses the three primary magneto-optic mechanisms for magnetic field sensing: Faraday effect, magnetic fluid, and magnetostrictive materials. We evaluate their advantages and disadvantages, with Faraday effect relying on the Verdet constant and facing complexity in measurement elements. FBG magnetic sensing with magnetic fluid shows promising sensitivity and versatility but is challenged by optical loss-induced errors. Magnetostrictive materials provide robustness but exhibit limited linearity. Future research should focus on addressing these challenges to enhance the reliability of FBGs for magnetic sensing. The findings highlight the exceptional potential of FBGs in advancing magnetic field sensing applications. 2023 Elsevier Ltd